Re-Irradiation for Recurrent Head and Neck Squamous Cell Carcinoma after Primary Radical Therapy - Pellizzon, Antonio Cassio Assis; Fogaroli, Ricardo Cesar; Silva, Maria Letícia Gobo; Castro, Douglas Guedes de; Godin, Guilherme; Chen, Michael (Journal of Diseases, 2015)
Introduction: Loco-regional failures, recurrence or second primary after radiotherapy (RT) is a significant problem in head and neck cancer (HNC) and represent a challenge. Methods: 39 patients were referred to the Radiation Oncology Department, A. C. Camargo Cancer Center, Sao Paulo, Brazil between 2007 to 2012 to have a second new course of RT (Re-RT) to a previous irradiated area in the head and neck. Results: Median age of patients was 53.8 (range, 31-74) years. Twenty four (61.5%) patients had surgery and Re-RT. The first radiation course dose ranged from 45 Gy to 72 Gy (median 60.0 Gy) and the median interval between the initial and second radiation course was 32 (range, 9-146) months. The median follow-up was 2.6 (range, 0.5-5.9) years. The 2- and 5-year actuarial OS, PFS and LC rates were 76.0%, 38.6%, 83.8%, 75.0%, 27.0% and 14.0%, respectively. Re-RT with IMRT when compared to other techniques showed PFS and LC advantages, p= 0.018 and p=0.019, respectively, confirmed by Cox regression multivariate - HR=6.08 (p= 0.020, 95% CI: 1.331- 27.767). Major toxicity occurred in 14 (35.9%) patients and eye observed no carotid artery blowout in this series. Conclusion: Re-RT should be offered for patients who are not suitable for surgery or for those with marginal resections, with a clear understanding that survival is poor and many of these patients will suffer severe radiation-related insults to their quality of life, during and after treatment.